Delivering Value Creation Through Integrated Finance Improvement Initiatives, Vision, and Core Values Internalization: A Case Study of SME Business Coaching - Dharmawan, Fredi; Fachrizah, Hilda (AIBPM Publisher, 2021)
SMEs have a significant contribution to the stability and development of the Indonesian economy but are not balanced by the productivity of the SMEs themselves. This problem can be solved if Business Coaching is carried out with accurate business analysis or strategy. This paper discusses a business coaching program for one of the potential SMEs that runs a contractor, interior design, and special furniture business. Business coaching focuses on three main areas, namely, financial, organizational, and human resources aspects. Business Coaching for CV Jati Indah Abadi is qualitative case study research. The business analysis used is Business Model Canvas, PESTEL, Porter's Five Forces, Segmenting Targeting and Positioning, Marketing Mix, VRIO, SWOT and TOWS, and Pareto Analysis. Based on the results of the analysis, CV Jati Indah Abadi has not implemented a financial planning system, budgeting, recording, monitoring, and evaluation of financial performance. Therefore, the author provides training on cash management, the use of project budgets, and transaction recording applications for preparing financial reports. The vision and values are also determined, so that it is expected to motivate and increase employee loyalty, including encouraging SME owners to further optimize their business potential by continuing to make improvements and implement best practices. Keywords: Business Coaching; Competitive Improvement; Human Resources; Organization; SMEs